Human induced pluripotent stem cells (hiPSC), enveloped in elastin-like recombinamers for cell therapy of type 1 diabetes mellitus (T1D): preliminary data - Montanucci, Pia; Pescara, Teresa; Greco, Alessia; Basta, Giuseppe; Calafiore, Riccardo (Frontiers in Bioengineering and Biotechnology, 2023)
Therapeutic application and study of type 1 diabetes disease could benefit from the use of functional β islet-like cells derived from human induced pluripotent stem cells (hiPSCs). Considerable efforts have been made to develop increasingly effective hiPSC differentiation protocols, although critical issues related to cost, the percentage of differentiated cells that are obtained, and reproducibility remain open. In addition, transplantation of hiPSC would require immunoprotection within encapsulation devices, to make the construct invisible to the host’s immune system and consequently avoid the recipient’s general pharmacologic immunosuppression. For this work, a microencapsulation system based on the use of "human elastin-like recombinamers" (ELRs) was tested to envelop hiPSC. Special attention was devoted to in vitro and in vivo characterization of the hiPSCs upon coating with ERLs. We observed that ELRs coating did not interfere with viability and function and other biological properties of differentiated hiPSCs, while in vivo, ELRs seemed to afford immunoprotection to the cell grafts in preliminary in vivo study. The construct ability to correct hyperglycemia in vivo is in actual progress.